Inconsistencies in SURE models : computational aspects - Kontoghiorghes, Erricos John (My University, 2000)
The solution of the SURE model with singular variance-covariance matrix results in redundancies and possibly inconsistencies among the observations of the model. A numerical procedure is proposed and investigated that generates a consistent model from an inconsistent one. The use of SVD has been used to compute the various factorizations arising in the solution of the SURE model when treated as a generalized linear least squares problem.
Keywords: Least squares; Kronecker products; Analysis of variance; Analysis of covariance